Flexible control for power‐sharing in the CHB‐based SST under voltage unbalance conditions. Issue 11 (18th June 2021) - Babaei, Mehdi; Ghandehari, Reza
Abstract: Solid‐state transformers (SSTs) have flexible capabilities to improve the power quality issues. These improvements impose disturbances into the SST converters that require proper control algorithms. In this paper, the problems of the unequal active power flow in different phases of the SST due to the grid voltage unbalance conditions and the negative sequence current injection are discussed, and an effective method is proposed to equally sharing the active powers between the SST clusters by creating an optimum zero sequence current. Based on the power dependencies, an analytical vector for the zero‐sequence current is proposed, which can equally share the power among the SST clusters and balance the HVDC‐link voltages. Also, the proposed control strategy by using PIR controllers can achieve the zero‐sequence current based on a direct current control method. The provided equal power‐sharing among the clusters is kept in the considerable unbalanced voltage of the grid and prevents the SST outage during faults. The simulation and experimental results confirm the proposed control method to equalise the power‐sharing among the SST clusters and voltage equalisation of the HVDC‐links while the SST tries to improve the grid voltage unbalance and in the fault conditions of the grid.